The Tilawati Method in Qur'an Reading Learning to Enhance the Quality of Memorizing the Qur'an in Islamic Boarding Schools - Abdurrahman; Ikhwan, Afiful; Arifin, Syamsul (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to analyze the implementation of the Tilawati method in learning to read the Qur'an and memorizing the Qur'an in Islamic boarding schools. This study uses a qualitative and case study approach to explore the application of the Tilawati method in learning the Qur'an and its impact on the quality of student memorization in Islamic boarding schools. Data was collected through semi-structured interviews with ustadz, students, and pesantren administrators, as well as participant observation and documentation. Data analysis includes data collection stages, condensation, data presentation, and conclusion drawing and verification. The validity of the data is ensured through source, technique, and time triangulation. The learning strategies applied include talaqqi and musyafahah, gradual learning according to volume, the use of Tilawati tones (rost), routine evaluation, and the integration of learning in students' daily lives. The study results show that these strategies effectively build a strong and systematic foundation of Qur'an reading before students enter the Qur'an memorization program. Students who have completed the Tilawati program can read the Qur'an well, tartil, and a few Tajweed errors, so memorizing the Qur'an becomes faster and more qualified. This success is also supported by a periodic evaluation system, muroja'ah activities, and integrating learning into daily activities such as congregational prayers and joint recitations.